PENGARUH KEMUDAHAN, KEAMANAN, KETANGGAPAN, HARGA DAN REPUTASI PERUSAHAAN TERHADAP KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN PRODUK KERAJINAN DANBO SECARA ONLINE - Randika Fandiyanto; Raden Andi Sularso; Bambang Irawan (Growth, 2017)
The high business competition is currently pushing many industries of Micro and Small Medium Enterprises to continue to innovate both the attributes of products and marketing, currently pushed UMKM to enter the online business through e-commerce into a promising opportunity in the chain selanjuanua network. This study aims to describe the ease, security, responsiveness, price, reputation, trust and decision of Danbo handicraft sales at Trebungan Handicraft House, Situbondo Regency, beside that this research is also explanatory research which analyze each exogenous variable to variable Endogenous This research was conducted in Situbondo Regency precisely through Trebungan Home Industry, with 634 people and technique of sampling using proportional random sampling "based on time division, with the number of samples selected as 270 respondents from various regions in Indonesia namely Java, Sulawesi , Kalimantan, Sumatra, Maluku, Papua and Nusa Tenggara. Analysis of model data using structural equation model (SEM), the results showed for the first test. Normality test does not occur. Normality, Outlier and Multicoliner. The fit fitness model (GOF) also has good model conformity and for hypothesis test results. Hypothesis 1 received where the variable Ease (X1), Security (X2), Response (X3) Price (X4) and Reputation (X5) has a significant effect on Trust (Y1). Hypothesis 6 is rejected, it can be concluded that the Ease (X1) variable has no significant effect on the Purchase Decision variable (Y2). Hypothesis 7 is accepted. Namely Security variables have a significant negative effect on Purchase Decision (Y2). Hypothesis 8 rejected, concluded that the variable Response (X3) has no significant effect on Purchase Decision (Y2). Hypothesis 9 is rejected, namely that Price variable (X4) has no significant effect on Purchase Decision (Y2). Hypothesis 10 is accepted. It is concluded that the Reputation variable (X5) has a significant negative effect on Purchase Decision (Y2), Hypothesis 11 accepted, namely variable of Trust (Y1) have a significant effect on Purchase Decision (Y2).